PERAN MEDIASI MOTIVASI PADA PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA DI KABUPATEN TEMANGGUNG - Isro Hendar Saputra; Amin Yusuf; Muhammad Khafid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Middle School teachers in Temanggung District have various problems including a less supportive work environment, low motivation in teaching, insufficient application of Reward and Punishment, resulting in less than optimal teacher discipline. This study aims to determine the influence of leadership on motivation, leadership on teacher discipline, work environment on teacher work motivation, work environment on teacher discipline, motivation on teacher discipline, the influence of leadership, work environment on teacher discipline through motivation and the role of motivation in mediating the influence of leadership and work environment on teacher discipline. This study uses a descriptive research model with a quantitative approach with a population of 147 and sampling using proportional random sampling technique resulting in a sample size of 108. Data collection in this study uses a questionnaire method, prerequisite tests using validity and reliability tests, classical assumption tests using descriptive statistical tests, normality tests, linearity tests, heteroscedasticity tests, and multicollinearity tests. While hypothesis testing uses regression tests, path analysis model 1 and path analysis model 2 tests, and Sobel tests. The results of the study obtained a coefficient value of leadership on motivation of 0.412, a coefficient of work environment on motivation of 0.223 with an error value1 of 0.8831, a coefficient of leadership on work discipline of 0.251, a coefficient of work environment on work discipline of 0.139, and a coefficient of motivation on work discipline of 0.823 with an error value2 = 0.6041. After conducting regression tests, path analysis model 1 and path analysis model 2 tests, and Sobel test, it is concluded that there is a significant influence of leadership on motivation, leadership on teacher discipline, work environment on motivation, work environment on teacher discipline, motivation on teacher discipline, motivation on teacher discipline, and all independent variables have a direct effect on the dependent variable. Motivation as a mediating variable indirectly influences the independent variables on the dependent variable.